Crystallization of zirconia based thin films. Issue 28 (28th July 2015) - Stender, D.; Frison, R.; Conder, K.; Rupp, J. L. M.; Scherrer, B.; Martynczuk, J. M.; Gauckler, L. J.; Schneider, C. W.; Lippert, T.; Wokaun, A.
<x xml:space="preserve">Abstract</x> Recrystallization kinetics of pulsed laser deposited amorphous 3YSZ and 8YSZ thin films leading to large differences in grain growth.